Analysis of RNA splicing defects in PITX2 mutants supports a gene dosage model of Axenfeld-Rieger syndrome - Semina Elena V; Murray Jeffrey C; Alward Wallace LM; Maciolek Nicole L; McNally Mark T (BMC, 2006)
Abstract Background Axenfeld-Rieger syndrome (ARS) is associated with mutations in the PITX2 gene that encodes a homeobox transcription factor. Several intronic PITX2 mutations have been reported in Axenfeld-Rieger patients but their effects on gene expression have not been tested. Methods We present two new families with recurrent PITX2 intronic mutations and use PITX2c minigenes and transfected cells to address the hypothesis that intronic mutations effect RNA splicing. Three PITX2 mutations have been analyzed: a G>T mutation within the AG 3' splice site (ss) junction associated with exon 4 (IVS4-1G>T), a G>C mutation at position +5 of the 5' (ss) of exon 4 (IVS4+5G>C), and a previously reported A>G substitution at position -11 of 3'ss of exon 5 (IVS5-11A>G). Results Mutation IVS4+5G>C showed 71% retention of the intron between exons 4 and 5, and poorly expressed protein. Wild-type protein levels were proportionally expressed from correctly spliced mRNA. The G>T mutation within the exon 4 AG 3'ss junction shifted splicing exclusively to a new AG and resulted in a severely truncated, poorly expressed protein. Finally, the A>G substitution at position -11 of the 3'ss of exon 5 shifted splicing exclusively to a newly created upstream AG and resulted in generation of a protein with a truncated homeodomain. Conclusion This is the first direct evidence to support aberrant RNA splicing as the mechanism underlying the disorder in some patients and suggests that the magnitude of the splicing defect may contribute to the variability of ARS phenotypes, in support of a gene dosage model of Axenfeld-Rieger syndrome.